Influence of skippable, non-skippable and product knowledge advertisements on consumer responses in purchasing products that appear in advertisements - Sinaga, Savrina Oktaviana; Leonardo, Austin; Anisa, Nurul; Diana, Febi Nur (Digital Business: Tren Bisnis Masa Depan, 2023)
The purpose of this study is to find out how skippable, non-skippable advertising and product knowledge affect customer response. The theory of advertising value (informativeness, credibility, entertainment, irritation) and consumer response theory (awareness, knowledge, likes, preferences, beliefs, purchases) are used. This study uses a quantitative approach and uses a survey as a type of explanatory research. fifty people answered using the Slovin formula. Closed-ended questionnaires, observations, literature, and literature studies are data collection methods. Data analysis was carried out through the data processing stage using SPSS, and statistical formulas were used to analyze the data. The results of this study indicate that there is an insignificant effect between YouTube advertisements and customer responses.